The role of infographics in improving the literacy of F2 phase students in Quiz.Zep-based AKM training with deep learning analysis - Trihastuti, Deviokti; Alfannasheera, Lathifa; Hadi, Bayu Prasetya; Sulistyorini, Dewi (COPE: Caraka Olah Pikir Edukatif, 2026)
The Minimum Competency Assessment (AKM) is designed to measure students' literacy and numeracy skills through text-based and visual questions. One form of presentation that demands high analytical skills is infographics because they combine text, numbers, and graphic elements in discourse paragraphs. For Phase F2 students, understanding infographics remains a challenge, so learning media that can adapt them to processing visual data is needed. This article aims to analyze the role of infographics in improving the literacy of Phase F2 students in AKM exercises based on Quiz.zep from a perspective. Deep Learning which emphasizes Mindful, Meaningful, and Joyful Learning. The method used was descriptive qualitative with observation, interviews, literature study, and documentation techniques. The study was conducted at SMA Negeri 1 Turi in grade XII (F2.1 and F2.2) with a total of 71 students. Data were analyzed through the stages of reduction, categorization, interpretation, and drawing conclusions. The results showed that the use of infographics through Quiz.zep improved students' visual literacy and numeracy, with an average score of 81.8 in grade F2.1 and 80 in grade F2.2. In addition, students were better able to interpret visual data, although they still faced difficulties in connecting complex text and graphics. Implementation of Deep Learning demonstrates more conscious student involvement (mindful), relevant (meaningful), and fun (joyful). Thus, the role of infographics and Quiz.zep effectively supports increased literacy while creating critical, reflective, and interactive learning experiences.